Uprooting an abscisic acid paradigm: Shoots are the primary source. (2nd June 2016) - McAdam, Scott A. M.; Manzi, Matías; Ross, John J.; Brodribb, Timothy J.; Gómez-Cadenas, Aurelio
ABSTRACT: In the past, a conventional wisdom has been that abscisic acid (ABA) is a xylem-transported hormone that is synthesized in the roots, while acting in the shoot to close stomata in response to a decrease in plant water status. Now, however, evidence from two studies, which we have conducted independently, challenges this root-sourced ABA paradigm. We show that foliage-derived ABA has a major influence over root development and that leaves are the predominant location for ABA biosynthesis during drought stress.